2016
DOI: 10.1007/s00213-016-4460-1
|View full text |Cite
|
Sign up to set email alerts
|

BDNF concentrations and daily fluctuations differ among ADHD children and respond differently to methylphenidate with no relationship with depressive symptomatology

Abstract: Our data support a reduction in BDNF in untreated ADHD due to the lower concentrations in PHI/CD children, which is similar to other psychopathologic and cognitive disorders. MPH decreased BDNF only in the PAD group, which might indicate that BDNF is not directly implicated in the methylphenidate-induced amelioration of the neuropsychological and organic immaturity of ADHD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 72 publications
2
15
1
Order By: Relevance
“…These markers have essential roles in promoting children’s growth and development [ 70 , 71 , 72 ]. In contrast to the BDNF that was lower in newly diagnosed ADHD patients [ 73 ], this study found that the serum levels of IGF-1 and IGFBP-3 were within the normal range in newly diagnosed primary school patients with ADHD. These results indirectly confirmed that the secretion and role of endogenous growth hormones were normal in newly diagnosed primary school patients with ADHD.…”
Section: Discussioncontrasting
confidence: 71%
“…These markers have essential roles in promoting children’s growth and development [ 70 , 71 , 72 ]. In contrast to the BDNF that was lower in newly diagnosed ADHD patients [ 73 ], this study found that the serum levels of IGF-1 and IGFBP-3 were within the normal range in newly diagnosed primary school patients with ADHD. These results indirectly confirmed that the secretion and role of endogenous growth hormones were normal in newly diagnosed primary school patients with ADHD.…”
Section: Discussioncontrasting
confidence: 71%
“…Several case-control studies have indicated that the peripheral BDNF levels in both serum and plasma do not differ significantly between patients with ADHD and controls [13,15,16]. A recent meta-analysis revealed no significant difference between peripheral BDNF levels in ADHD patients and control groups [14].…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that dysfunctional BDNF is a possible contributor to the pathology and symptoms of ADHD [11]. Nonetheless, the findings about whether peripheral levels of BDNF can serve as reliable ADHD biomarkers were inconsistent among studies [12,13,14,15,16]. One possible explanation for this inconsistency is the moderating effect that gender has on the relationship between BDNF and ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found decreased serum BDNF in ADHD patients as compared with healthy controls, and importantly, further decreases in serum BDNF with chronic methylphenidate treatment in children with ADHD-PI but not in children with ADHD-C. There have been conflicting findings with regard to the impact of methylphenidate on BDNF levels, and thus the significance of the aforementioned finding remains to be determined [178].…”
Section: Pharmacotherapy Studiesmentioning
confidence: 97%